Exploitation of deep-sea resources: the urgent need to understand the role of high pressure in the toxicity of chemical pollutants to deep-sea organisms - Mestre, Nélia C.
The advent of industrial activities in the deep sea will inevitably expose deep-sea organisms to potentially toxic compounds. Although international regulations require environmental risk assessment prior to exploitation activities, toxicity tests remain focused on shallow-water model species. Moreover, current tests overlook potential synergies that may arise from the interaction of chemicals with natural stressors, such as the high pressures prevailing in the deep sea. As pressure affects chemical reactions and the physiology of marine organisms, it will certainly affect the toxicity of pollutants arising from the exploitation of deep-sea resources. We emphasize the need for environmental risk assessments based on information generated from ecotoxicological trials that mimic, as close as possible, the deep-sea environment, with emphasis to a key environmental factor - high hydrostatic pressure.